Proximate, minerals, vitamins, and antinutrients and their correlations in the leaves of Senecio biafrae accessions - Baiyeri, Samuel (Journal of Agricultural Sciences (Belgrade), 2023)
Micronutrient malnutrition is a global challenge of both the elites and the resource-poor. There are promising opportunities for combating it through the consumption of neglected and under-utilized leafy green vegetables. Senecio biafrae is an underutilized and nutrient-dense green leafy vegetable with huge nutritional and health potentials that have remained under-exploited. It has received very limited research and funding attention. The aim of this research was to evaluate the proximate, minerals vitamins, anti-nutrients and their correlations among the accessions of this veggie. Leaf samples of the accessions were collected and assayed through standard biochemical methodologies. Results showed that the accessions differed significantly (p<0.05) in the nutritional and anti-nutritional traits studied. The accessions were rich in potassium, magnesium, calcium, low in fat and anti-nutrients. The Pearson correlations results showed that most of the nutritional parameters either had inverse or no relationships with anti-nutrients. Crude protein showed significant (p<0.01) positive correlations with dry matter (0.90**) and a negative correlation with cyanogenic glycoside (-0.90**). Cyanogenic glycoside showed significant (p<0.01) negative correlations with potassium (-0.63**), calcium (-0.66**) and dry matter (-044*). Nitrate showed no significant (p>0.05) relationship with any nutritional parameter. Oxalate and tannin showed no significant relationship with the vitamins. Phytate and tannin showed no significant relationship with the proximate qualities and the minerals. The results showed that Senecio biafrae leaf is nutrient-dense and could help to mitigate the effects of micronutrient deficiencies. The variations and relationships among the nutritional and anti-nutritional parameters could enhance meaningful selection and its nutritional quality improvement through breeding.